Pelaksanaan Kampanye Pemilihan Kepala Daerah (Pilkada) dalam Perspektif Hak Asasi Manusia (Studi Kasus di Provinsi Kalimantan Barat) - Okky Chahyo Nugroho (Badan Strategi Kebijakan Hukum, 2014)
Election is the momentum for the community to voice communication rights are implemented through political campaigns. Politics in the election campaign is one important step in the implementation of procedural democracy . In practice, political campaigns are conducted in some areas yet despite the sentiments which tend to be discriminatory . Issues raised in this study is how the picture of the practice of regional head election campaigns (elections ) in West Kalimantan; picture of how the election campaign nuanced pattern of human rights; how the efforts of the government and election organizers in addressing and preventing practices that are not nuanced human rights campaign . The purpose of research is to describe the practice of election campaigns that occurred in the province of West Kalimantan and the factors supporting the election campaign nuanced discrimination ; obtain a pattern of human rights nuanced election campaign ; know the government's efforts in addressing and organizing election campaign practices are not nuanced human rights . As for the substance of human rights that the boundaries in this study include : the right not to be treated in a discriminatory manner in the course of the campaign . The method used in this study using a qualitative approach to the descriptive nature of the research . Techniques of data analysis and information gathered from informants and interviewees then performed a qualitative analysis of the substance , context , and the relationship between the audience campaigners from the aspect of human rights. Based on field data still use the election campaign practices of political identities (ethnic , religious , and regional) as a strategy in the campaign . Elements of the campaign include dilakuakan substance , context , and relationships in the campaign was marred by discrimination regionalism , ethnicity , and religion to seek public sympathy.